Functionality and characterization of intermediate wheatgrass in spontaneous fermentation and end product quality - Iorga, Brianna (Kansas State University, 2024)
Intermediate wheatgrass (IWG) is a perennial wheat and found to have better environmental effects compared to annual plants. Soil nutrition is increased, the plant is drought and disease tolerant, and there is a decrease in labor input. There are also nutritional benefits found in IWG, such as a higher protein, fiber, and mineral content than that of wheat. IWG yield and kernel size is smaller, when compared to wheat though. But the biggest drawback is the decreased amount of high-molecular-weight glutenin subunits (HMW-GS). Throughout various research IWG has been tested in bread products and due to lack in HMW-GS has a poor performance. The Land Institute has been spearheading breeding efforts however and has made improvements to the mixing quality. This study evaluated the breeding efforts and measured the performance of four IWG cultivars in bread making, where one cultivar was specifically bred for mixing quality (MQ). Mixograph parameters and baking trial results were found to be significantly different for MQ. The breeding efforts were found to be successful as dough quality, mixing tolerance, bread volume, and number of cells all increased. The high protein, ash, and starch content indicated IWG would be a suitable candidate in sourdough fermentation. The objective of this study was to determine the performance of IWG in a spontaneous fermentation process, compared to a whole wheat (WW) flour. Three fermentation trials were conducted to determine processing, acidification kinetics, lactic acid bacteria (LAB) and metabolite evolution. IWG was found to have a slightly higher Vmax than WW but achieved higher final TTA. The fermentation quotient (FQ) and lactic acid production were also found to be higher for IWG, in agreement with high LAB enumeration. The sourdough was also utilized in a wheat-based bread trial and were analyzed for specific volume, firmness, acidity, and a first day to visual mold analysis. The IWG bread was found to be more acidic but had no negative effects to the product quality including volume and post-bake firmness. The spontaneously fermented sourdoughs were also evaluated in a sensory analysis. IWG sourdough or whole wheat sourdough was added to a wheat-based formulation and evaluated with a degree of difference (DOD) test and Just About Right scale (JAR) (N= 50 responses in 2 sessions). This was to determine how similar or different IWG was from WW and determine how the breads do or do not meet consumer expectations. Four attributes (appearance, aroma, flavor, and texture) and overall questions were analyzed for both DOD and JAR. An action criteria of 2 was chosen for the DOD, signifying that below 2 there was low risk consumers would notice a difference. IWG had a DOD average of 2.4. However, panelists also found differences in a WW blind control (1.8). This is an indication that panelists were looking for a difference, thus actual difference can be assumed to be smaller. Both IWG and WW had an average JAR score above 3 (“meets expectations”), indicating that despite the differences noticed IWG still met consumer’s expectations. With formula optimization the samples could align more, allowing for the potential use of IWG in a sourdough process and wheat-based bread.
Keywords: Intermediate wheatgrass; Spontaneous fermentation; Sourdough; Dough analysis; Bread quality; Sensory evaluation